Fracture resistance and failure modes of CEREC endo-crowns and conventional post and core-supported CEREC crowns - Chia-Yu Chang; Jau-Shing Kuo; Yang-Sung Lin; Yen-Hsiang Chang (Elsevier, 2009)
The purpose of this in vitro study was to compare the fracture resistance and failure modes of CEREC endo-crowns with the CEREC classic designed crown supported with glass fiber-reinforced composite posts and composite cores. The influences of thermal cycling and fatigue loading on both types of restorations were also investigated. Materials and methods: Twenty extracted intact maxillary premolars were randomly divided into two groups (C and E). The crown portion of the specimens was removed to 1.5 mm above the cementoenamel junction (CEJ). All specimens were endodontically treated with a nickel-titanium rotary system and obturated with gutta-percha by a vertical compaction technique. In group C (n = 10), teeth were restored with glass fiber-reinforced composite posts and composite cores with a 1.0-mm wide circumferential shoulder margin at the CEJ and a 1.5-mm ferrule. In group E (n = 10), teeth were prepared for fabrication of CEREC endo-crowns. Both types of ceramic crowns were produced from ProCAD ceramic blocks utilizing a CEREC 3D CAD-CAM unit, and these were bonded to the preparations with an adhesive system and composite resin cement. Teeth were thermally cycled (2000 cycles of 5°C/55°C with a dwell time of 30 seconds,) and fatigue loaded (20,000 cycles at 5 kg and 3 Hz) in a custom-made fatigue simulator. All specimens were loaded in a universal testing machine with a cross-head speed of 0.5 mm/s until fracture occurred. Fracture resistance and failure modes were statistically evaluated with a t test and χ2 test. Results: The mean fracture resistance ± standard deviation was recorded as follows: 1163.30±163.15 N for group C and 1446.68±200.34 N for group E. A significant difference was found between groups with respect to fracture resistance (P < 0.05). Regarding failure modes, most specimens of both groups exhibited unfavorable fractures, and no significant difference was found between the two groups. Conclusion: The bonded ceramic endo-crowns showed a significantly higher fracture resistance than the classic reinforced and designed group and, therefore, offer a feasible alternative for severely damaged teeth.